Religious Moderation In The Quranic Story Of Prophet Joseph And Its Education Values : الاعتدال الديني في قصة يوسف القرآنية ومضامينه التربوية - Rokim, Syaeful; Muslim, Muslim; Supriadi, Cecep; Al-Shahri, Shalih Ali (ZAD Al-Mufassirin, 2024)
This study aims to examine the concept of religious moderation embedded in the story of Prophet Yusuf as narrated in the Qur'an, as well as to explore the educational values that can be implemented in daily life. This research employs a qualitative method with a thematic interpretation approach. Additionally, this study explores the perspectives of scholars on the educational values found in the narrative. The results of the study indicate that the story of Yusuf presents a range of essential values, including steadfastness in religious principles, balance between religious obligations and worldly activities, the practice of tolerance and reconciliation, and the importance of dialogue and mutual understanding. Yusuf teaches us that strong faith and self-control can help individuals overcome various life challenges. This study concludes that the story of Prophet Yusuf provides valuable lessons on religious moderation that can be integrated into moral and spiritual education. Values such as adherence to principles, balance between religion and life, tolerant behavior, and open dialogue are crucial for building a harmonious and respectful society. Therefore, teaching and applying these values in daily life is essential for achieving positive personal and social development.